Cost Systems for Planning, Decisions, and Controls: Concepts and Techniques (Book). - Burns, Thomas J.; Hartman, Bart P. (The Accounting Review, 1980)
Reviews the book "Cost Systems for Planning, Decisions, and Controls: Concepts and Techniques," by Felix P. Kollaritsch.